69 The Experimental Methodology and Comparators Used For In Vivo Hernia Mesh Testing; A Ten-Year Scoping Review:. (12th October 2021) - Whitehead-Clarke, T; Karanjia, R; Banks, J; Beynon, V; Parker, S; Sanders, D; Mudera, V; Windsor, A; Kureshi, A
Abstract: Aim: Before being marketed, hernia mesh must undergo in vivo testing, which often includes biomechanical and histological assessment. Currently there are no universal standards for this testing and methods vary greatly within the literature. A scoping review of relevant studies was undertaken to analyse the methodologies used for in vivo mesh testing. Method: Medline and Embase databases were searched for relevant studies. 513 articles were identified, and 231 duplicates excluded. 126 papers were included after abstract and full text review. Data extraction was undertaken using standardized forms. Results: Mesh is most commonly tested in rats (53%). 78% of studies involve the formation of a defect; in 52% of which the fascia is not opposed. The most common hernia models use mesh to bridge an acute defect (50%). Tensile strength testing is the commonest form of mechanical testing (63%). Testing strip widths and test speeds vary greatly (4-30mm and 1.625-240mm/minute respectively). There is little consensus on which units to use for tensile strength testing. Collagen is assessed for its abundance (54 studies) more than its alignment (18 studies). Alignment is not measured quantitatively. At least 21 histological scoring systems are used for in vivo mesh testing. Conclusions: The current practice of in vivo mesh testing lacks standardisation. There is significant inconsistency in every category of testing, both in methodology and comparators. We would call upon hernia organisations and materials testing institutions to discuss the need for a standardized approach to this